The Impact of Workplace Diversity on Innovation: The Moderating Effects of Transactive Memoryand Inclusion Climate - haji Ushimaru; Mehran Doulatabadi (Bina Nusantara University, 2022)
With the progress of globalization, diversity management, such as how to manage employees with different genders, races, languages, values, etc., has become an important issue even in Japanese companies, which have traditionally been dominated by male regular employees. This study examined the effects of bio-demographic diversity and task-related diversity on innovation in the workplace, and the moderating effects of inclusion climate and transactive memory. Four hypotheses were proposed and the questionnaire surveys from 173 Japanese employees in various companies were statistically analyzed. The results showed that task-related diversity, which is an internal characteristic of human attributes such as work experience, educational experience, and values, was a factor that promoted innovation. In addition, transactive memory, which is a memory system of knowledge about who knows what in the workplace, was found to strengthen the positive relationship between task-related diversity and innovation as the higher it was. In addition, although inclusion climate had no moderating effect between diversity and innovation, it had a significantly positive direct impact on innovation. It was suggested that creating a climate of inclusion, independent of increasing the degree of diversity, is important for innovation in the workplace.